Guided Lithium Deposition by Surface Micro‐Patterning of Lithium‐Metal Electrodes. Issue 21 (24th August 2018) - Kim, Yun‐Jung; Jin, Hyun S.; Lee, Dong‐Hyun; Choi, Jaeho; Jo, Wonhee; Noh, Hyungjun; Lee, Jinhong; Chu, Hyunwon; Kwack, Hobeom; Ye, Fangmin; Lee, Hongkyung; Ryou, Myung‐Hyun; et al.
Abstract: Uncontrolled lithium (Li) deposition has hampered the evolution of Li‐metal electrode‐based Li‐batteries. In this work, we report the differences of a guided Li deposition with a size change of the square hole micro‐patterns carved on the Li‐metal surface with two different dimensions using a simple stamping method. Li deposition is preferentially initiated on the top edge for the smaller pattern and on the bottom for the larger pattern. Although the two patterns lead to a more uniform utilization of the Li, the larger pattern shows a higher cycling stability within a LiFePO4 /Li cell than that of the smaller one indicating that initiating the Li deposition from the bottom of the hole is more efficient in confining the deposited Li. Based on the impedance analysis of the compressed Li electrodes, we suggest that the guided Li deposition on the bottom of the hole is attributed to a large contrast in the resistance of native surface passivation layer between the top and hole surfaces. This improved understanding can further advance guided Li deposition induced by surface patterns for high performance Li‐metal batteries. Abstract : As a model study for understanding the guiding effect of Li‐metal deposition to specific sites on the patterns, two different sized square hole patterned Li‐metal electrodes (MP‐Lis) are manufactured. It demonstrates that the change in the passivation film on the Li surface driven by the mechanical deformation is a key factor to induce the guided Li deposition of MP‐Lis, though the shapes of patterns are the same.